2012
DOI: 10.1074/jbc.c112.403048
|View full text |Cite|
|
Sign up to set email alerts
|

Sirtuin 2 (SIRT2) Enhances 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Nigrostriatal Damage via Deacetylating Forkhead Box O3a (Foxo3a) and Activating Bim Protein

Abstract: Background:The functional role of SIRT2 in the MPTP model of Parkinson disease is not known. Results: Deletion of SIRT2 rescues MPTP-induced nigrostriatal damage by increasing acetylated Foxo3a levels, decreasing Bim expression, thereby preventing apoptotic pathways. Conclusion: SIRT2 deacetylates Foxo3a, increases Bim expression, and induces nigrostriatal damage. Significance: SIRT2 deletion is protective in the MPTP model of Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 14 publications
(2 reference statements)
1
23
0
2
Order By: Relevance
“…While the exact mechanism for reducing α-synuclein-A53T-mediated cell death is not known, these compounds decreased the number but increased the size of α-synuclein aggregates in a cellular model. A recent study validated these observations showing that genetic deletion of SIRT2 is protective in a chemically induced mouse model of PD using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) 77 . The proposed mechanism is that SIRT2 becomes active as a response to MPTP-induced stress causing Foxo3a deacetylation, which leads to increased levels of the pro-apoptotic factor Bim and neuronal death 77 .…”
Section: Parkinson's Diseasementioning
confidence: 66%
See 2 more Smart Citations
“…While the exact mechanism for reducing α-synuclein-A53T-mediated cell death is not known, these compounds decreased the number but increased the size of α-synuclein aggregates in a cellular model. A recent study validated these observations showing that genetic deletion of SIRT2 is protective in a chemically induced mouse model of PD using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) 77 . The proposed mechanism is that SIRT2 becomes active as a response to MPTP-induced stress causing Foxo3a deacetylation, which leads to increased levels of the pro-apoptotic factor Bim and neuronal death 77 .…”
Section: Parkinson's Diseasementioning
confidence: 66%
“…A recent study validated these observations showing that genetic deletion of SIRT2 is protective in a chemically induced mouse model of PD using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) 77 . The proposed mechanism is that SIRT2 becomes active as a response to MPTP-induced stress causing Foxo3a deacetylation, which leads to increased levels of the pro-apoptotic factor Bim and neuronal death 77 . Major mechanisms that have been proposed for SIRT1 and SIRT2 in Parkinson's disease pathogenesis are diagrammed in Figure 3.…”
Section: Parkinson's Diseasementioning
confidence: 66%
See 1 more Smart Citation
“…Sirt2 may also function to regulate autophagy and mitophagy under α-synuclein toxicity [108] . A recent study has shown that Sirt2 enhances MPTPinduced nigrostriatal damage via deacetylating FoxO3a and activating Bim protein [109] . However, this study was recently withdrawn, adding some controversy to the roles of Sirt2 [110] .…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…A recent study has shown that Sirt2 enhances MPTPinduced nigrostriatal damage via deacetylating FoxO3a and activating Bim protein [109] . However, this study was recently withdrawn, adding some controversy to the roles of Sirt2 [110] . As such, further research is warranted.…”
Section: Parkinson's Diseasementioning
confidence: 99%